Analytical methods for the effect of anode nitrogen concentration on performance and voltage consistency of proton exchange membrane fuel cell stack. (1st November 2022) - Chen, Dongfang; Pei, Pucheng; Ren, Peng; Song, Xin; Wang, He; Zhang, Lu; Wang, Mingkai
Abstract: Buckets effect remains one of the most important factors limiting the fuel cell stack performance and lifetime. An experiment on a 16-cell stack with decreasing hydrogen concentration is conducted to investigate the effect of anode nitrogen concentration on stack performance and voltage consistency. The mean voltage decay rate of the stack is only 6% at the current density of 1.0 A cm −2, but the decay rate of the single cell with minimum voltage reaches up to 18%. The voltage standard deviation of the fuel cell stack increases by about 8 mV with the decrease in hydrogen concentration from 100% to 85%. Results show that the local voltage standard deviation is as high as 30 mV at 85% hydrogen concentration when the 16 cells are divided into four groups. The influence of local voltage consistency on the overall voltage consistency is further studied. The local voltage consistency can be served as a reliable indicator of anode purge strategy. Moreover, the uneven gas distribution amongst the cells in the stack can be analyzed and effectively detected, according to the local voltage consistency analysis with the experiment of anode nitrogen doping. Highlights: Influence of anode nitrogen concentration on voltage consistency is studied. Local voltage consistency analysis method of the stack is proposed. Influence of local voltage consistency on the stack is analyzed. New anode purge strategy based on local voltage consistency is provided. Local voltage consistency can be used to evaluate gas distribution of the stack.